Long-term Clinical Outcomes of Pars Plana Versus Anterior Chamber Placement of Glaucoma Implant Tubes. Issue 5 (May 2018) - Qin, Vivian L.; Kaleem, Mona; Conti, Felipe F.; Rockwood, Edward J.; Singh, Annapurna; Sood-Mendiratta, Shalini; Sears, Jonathan E.; Silva, Fabiana Q.; Eisengart, Jonathan; Singh, Rishi P.
Abstract : Purpose: To compare long-term surgical outcomes and complications of pars plana (PP) tube implantation with conventional anterior chamber (AC) tube implantation. Materials and Methods: Records of patients undergoing glaucoma tube implant surgery at a single institution between 2007 and 2015 were retrospectively reviewed. Eyes were matched for glaucoma diagnosis and patient age. Demographics, baseline characteristics, and treatment outcomes were recorded. Surgical success was defined as intraocular pressure (IOP) between 6 and 21 mm Hg, no subsequent glaucoma surgeries performed, and at least light perception vision. Results: Fifty-seven eyes that underwent Ahmed or Baerveldt glaucoma drainage device surgery with PP tube placement were compared with 57 eyes with AC tube placement. Mean follow-up was 43.5 months in the PP group and 35.3 months in the AC group ( P =0.02). Forty-nine (86.0%) PP eyes and 46 (80.7%) AC eyes achieved surgical success ( P =0.45). At last follow-up, mean IOP decreased from 29.0 to 15.1 mm Hg in the PP group ( P <0.01) and from 32.7 to 15.6 mm Hg in the AC group ( P <0.01). Mean number of medications decreased from 2.9 to 1.1 in the PP group ( P <0.01) and from 2.8 to 1.3 in the AC group ( P <0.01). Mean IOP and number of medications were similar between PP and AC groups at baseline, last follow-up, and all interim time points ( P >0.05 for all). There were 16 complications in the PP group and 14 in the AC group ( P =0.67). Conclusions: Long-term results of glaucoma tube implant surgery with PP versus AC implantation shows effective IOP control with similar rates of surgical success.